Surgical technique for developing a rabbit model of congenital diaphragmatic hernia and tracheal occlusion - Mudri, M. (MethodsX, 2019)
The surgical model of congenital diaphragmatic hernia (CDH) has been utilized in exploring treatments and innovative therapies, such as tracheal occlusion (TO). The rabbit is an excellent surgical model compared to others due to lower cost, ease of care, short gestational period, and large litter size. This model is also ideal in studying lung hypoplasia of CDH because rabbit lung development is most similar to humans as alveolarization begins prior to birth and continues post-natally. However, the surgical technique in creating a rabbit model of CDH is quite difficult and information is lacking on how to establish this model. Therefore, the aim of this paper is to describe: • Surgical technique in establishing a rabbit model of CDH and TO; • Perioperative care for pregnant rabbit does.